The importance of vocabulary in language learning process - Karimova Shaxnozaxon Karimovna; Ibragimova Dinara (International Consortium of Education and Culture Research Studies, 2019)
This article considers about the interactive methods of teaching vocabulary at the educational establishments. We tried to analyze and generalize the scholars’ approaches towards the problem searched in our article. We hope this work can serve as a manual for teaches while teaching vocabulary.